Banned book club - Kim, Hyun Sook; Estrada, Ryan, 1980- (Iron Circus Comics, 2020)
"The autobiography of a South Korean woman's student days under an authoritarian regime, and how she defied state censorship. When Kim Hyun Sook started college in 1983 she was ready for her world to open up. After acing her exams and sort-of convincing her traditional mother that it was a good idea for a woman to go to college, she looked forward to soaking up the ideas of Western Literature far from the drudgery she was promised at her family's restaurant. But literature class would prove to be just the start of a massive turning point, still focused on reading but with life-or-death stakes she never could have imagined. This was during South Korea's Fifth Republic, a military regime that entrenched its power through censorship, torture, and the murder of protestors. In this charged political climate, with Molotov cocktails flying and fellow students disappearing for hours and returning with bruises, Hyun Sook sought refuge in the comfort of books. When the handsome young editor of the school newspaper invited her to his reading group, she expected to pop into the cafeteria to talk about Moby Dick, Hamlet, and The Scarlet Letter. Instead she found herself hiding in a basement as the youngest member of an underground banned book club. And as Hyun Sook soon discovered, in a totalitarian regime, the delights of discovering great works of illicit literature are quickly overshadowed by fear and violence as the walls close in. In BANNED BOOK CLUB, Hyun Sook shares a dramatic true story of political division, fear-mongering, anti-intellectualism, the death of democratic institutions, and the relentless rebellion of reading."--